2095. Infections in Burn Patients Receiving Extracorporeal Membrane Oxygenation (ECMO) at a Tertiary Military Medical Center. (26th November 2018) - Marcus, Joseph; Piper, Lydia; Ainsworth, Craig; Sams, Valerie; Okulicz, Jason; Barsoumian, Alice
Abstract: Background: Patients on ECMO are at higher risk for nosocomial infections. While several studies report on infections in ECMO patients, the epidemiology of infections in burn patients on ECMO has not been previously described. Methods: A retrospective chart review was performed on all patients on ECMO for >48 hours at Brooke Army Medical Center and the U.S. Army Institute of Surgical Research Burn Center between 2012 and 2017. Patient demographics, burn status, ECMO characteristics, and infection incidence during ECMO were captured. Statistical analyses comparing burn vs. nonburn patients were performed using chi-squared, Fisher's exact and Mann–Whitney U tests. Results: In comparison with those without diagnosed infections, infected patients had more days on ECMO (median [IQR] 16 [12–20] vs. 6.5 [5–10], P < 0.01) and longer hospitalization (median [IQR] 35 [24–54] vs. 23.5 days [8–45], P = 0.06), however survival to hospital discharge was no different (64% vs. 58%, P = 0.77). Burn patients trended toward more infections in their ECMO course (table). Conclusion: Infection is a common complication of ECMO and is associated with longer duration on ECMO and longer hospitalizations. Burn patients in this cohort were observed to have higher rates of infection compared with nonburn patients. Disclosures: All authors: No reported disclosures.